TNIP1 Regulates Cutibacterium acnes-Induced Innate Immune Functions in Epidermal Keratinocytes - Erdei, Lilla; Bolla, Beáta Szilvia; Bozó, Renáta; Tax, Gábor; Urbán, Edit; Kemény, Lajos; Szabó, Kornélia (Frontiers in Immunology, 2018)
Human skin cells recognize the presence of the skin microbiome through pathogen recognition receptors. Epidermal keratinocytes are known to activate toll-like receptors (TLRs) 2 and 4 in response to the commensal Cutibacterium acnes (C. acnes, formerly known as Propionibacterium acnes, P. acnes) bacterium and subsequently to induce innate immune and inflammatory events. These events may lead to the appearance of macroscopic inflammatory acne lesions in puberty: comedos, papules and, pustules. Healthy skin does not exhibit inflammation or skin lesions, even in the continuous presence of the same microbes. As the molecular mechanism for this duality is still unclear, we aimed to identify factors and mechanisms that control the innate immune response to C. acnes in keratinocytes, using a human immortalized keratinocyte cell line, HPV-KER, normal human keratinocytes (NHEK) and an organotypic skin model (OSM) . TNIP1, a negative regulator of the NF-κB signaling pathway, was found to be expressed in HPV-KER cells, and its expression rapidly induced in response to C. acnes treatment, which was confirmed in NHEK cells and OSMs. Expression changes were not C. acnes strain-specific. We found that the extent of expression was dependent on C. acnes dose. Bacterial-induced changes in TNIP1 expression were regulated by signaling pathways involving NF-κB, p38, MAPKK and JNK. Experimental modification of TNIP1 levels affected constitutive and C. acnes-induced NF-κB promoter activities and subsequent inflammatory cytokine and chemokine mRNA and protein levels. These results suggest an important role for this negative regulator in the control of bacterially induced TLR signaling pathways in keratinocytes. We showed that all-trans retinoic acid (ATRA) induced elevated TNIP1 expression in HPV-KER cells and also in OSMs, where TNIP1 levels increased through the epidermis. ATRA also reduced constitutive and bacterium-induced levels of TNFα, CCL5, and TLR2, while simultaneously increased CXCL8 and TLR4 expression. Based on these findings, we propose that ATRA may exhibit dual effects in acne therapy by both affecting the expression of the negative regulator TNIP1 and attenuating TLR2-induced inflammation. Overall, TNIP1, as a possible regulator of C. acnes-induced innate immune and inflammatory events in keratinocytes, may play important roles in the maintenance of epidermal homeostasis.